1999
DOI: 10.1055/s-2007-1016207
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Insulinlike Growth Factor Family in Nonpregnant Human Endometrium and at the Decidual:Trophoblast Interface

Abstract: The insulinlike growth factor (IGF) family is believed to be important in endometrial development during the menstrual cycle and in the process of implantation. The mitogenic, differentiative, and antiapoptotic properties of the IGFs and their binding proteins, as well as their spatial and temporal expression in cycling endometrium, suggest that they may participate in endometrial growth, differentiation, apoptosis, and perhaps angiogenesis. IGFBP proteases, which increase IGF bioavailability, have been locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…19 To our knowledge, this is the first study examining whether elevated levels of decidua-derived phIGFBP-1 in cervical fluid among unselected, asymptomatic women during early pregnancy are associated with an increased risk of subsequent spontaneous PTD. About one-third of the invited women participated in this study.…”
Section: Discussionmentioning
confidence: 86%
“…19 To our knowledge, this is the first study examining whether elevated levels of decidua-derived phIGFBP-1 in cervical fluid among unselected, asymptomatic women during early pregnancy are associated with an increased risk of subsequent spontaneous PTD. About one-third of the invited women participated in this study.…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that factors secreted by the invading trophoblast, such as human chorionic gonadotropin (hCG, CGB) and insulin-like growth factor (IGF)-II (IGF2), can modulate endometrial receptivity and the milieu at the implantation site (Giudice and Irwin, 1999;Licht et al, 1998;Fluhr et al, 2006). FasL (FASLG), typically inducing deathreceptor-mediated apoptosis, is secreted by first-trimester trophoblast cells and has been assumed to play a pivotal role in promoting a state of immune privilege during implantation (Abrahams et al, 2004;Uckan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Under the influence of different endocrine regulators, locally expressed and acting growth factors and cytokines are the main mediators during endometrial development (1,3,5,6). The insulin-like growth factor (IGF) system has been shown to be involved strongly in endometrial proliferation and differentiation, as well as during the process of implantation (4,5,(7)(8)(9)(10). In the human endometrium, the expression of IGF-I and -II is restricted to the stromal cells, showing unique changes during the menstrual cycle (5,8).…”
mentioning
confidence: 99%
“…The insulin-like growth factor (IGF) system has been shown to be involved strongly in endometrial proliferation and differentiation, as well as during the process of implantation (4,5,(7)(8)(9)(10). In the human endometrium, the expression of IGF-I and -II is restricted to the stromal cells, showing unique changes during the menstrual cycle (5,8). Insulin-like growth factor-I seems to be expressed preferentially in the mid to late proliferative and early secretory phase and is therefore believed to mediate the mitogenic actions of E 2 (11)(12)(13)(14).…”
mentioning
confidence: 99%